Bootstrapping I(1) data - Peter C. B. PHILLIPS (Institutional Knowledge at Singapore Management University, 2010)
A functional law is given for an I(1) sample data version of the continuous-path block bootstrap of Paparoditis and Politis (2001a). The results provide an alternative demonstration that continuous-path block bootstrap unit root tests are consistent under the null.